Creative Arts in crisis: Teaching and learning of creative arts in selected Public Primary Schools in Kumasi Metropolis. - Boafo, Agyeman Richmond. (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Arts .